Radiographic Investigation of The Relationship Between Dental Malocclusions And Dental Anomalies on the Turkish Population - Zeliha Uğur Aydın; Burak Sarıoğlu; Yasemin Nur Korkmaz (Cumhuriyet University, 2018)
Objectives: The aim of this study was to investigate the relationship between various dental anomalies and dental malocclusions/vertical growth patterns. Materials and Methods: The study was carried out on panoramic radiographs of 756 patients with a mean age of 15.46 ± 4.52 years. 64.6% (n = 488) of the total patients were female and 35.4% (n = 268) were male. The panoramic radiographs of the patients were detected for the following dental anomalies: supernumerary tooth, agenesis, transposition, microdontia, dileseration and taurodontism. The obtained data were analyzed using chi-square or Fisher exact tests at a significance level of 5%. Results: Impaction (14.4%) and microdontia (8.5%) were the most common anomalies.The prevalence of dental anomalies were the highest in skeletal Class II malocclusion (9.9%) and hypodivergent (11.6%) growth pattern (p˂0.05). Conclusion:The presence of an association between skeletal malocclusion/vertical growth pattern and dental anomalies was observed for tooth agenesis, impaction, transposition and taurodontism. Supernumerary tooth, microdontia and dilaceration were not significantly different among malocclusion groups.